The Escherichia Coli Hfq Protein: An Unattended DNA-Transactions Regulator - Cech, Grzegorz M.; Szalewska-Pałasz, Agnieszka; Kubiak, Krzysztof; Malabirade, Antoine; Grange, Wilfried; Arluison, Veronique; Węgrzyn, Grzegorz (Frontiers in Molecular Biosciences, 2016)
The Hfq protein was discovered in Escherichia coli as a host factor for bacteriophage Qβ RNA replication. Subsequent studies indicated that Hfq is a pleiotropic regulator of bacterial gene expression. The regulatory role of Hfq is ascribed mainly to its function as an RNA-chaperone, facilitating interactions between bacterial noncoding RNA and its mRNA target. Thus, it modulates mRNA translation and stability. Nevertheless, Hfq is able to interact with DNA as well. Its role in the regulation of DNA-related processes has been demonstrated. In this mini-review, it is discussed how Hfq interacts with DNA and what is the role of this protein in regulation of DNA transactions. Particularly, Hfq has been demonstrated to be involved in the control of ColE1 plasmid DNA replication, transposition, and possibly also transcription. Possible mechanisms of these Hfq-mediated regulations are described and discussed.